ECONOMIC VIABILITY AND ECOLOGICAL FRIENDLINESS OF MADRASAH EDUCATIONAL INSTITUTION IN REGION XII, PHILIPPINES - Dilangalen, A. K; Adam, Z. M (PEOPLE: International Journal of Social Sciences, 2019)
This study covered a total of 434 respondents from selected Madaris in the provinces of Cotabato and Maguindanao, Philippines, broken down as follows: 350 students, 70 Asatids, and 14 administrators.The general objective of the study was to investigate the economic viability and ecological friendliness of Madrasah educational institution operating in Mindanao Muslim communities. Specifically, it sought to determine the profiles of the Asatids, level of adequacy of existing resource capabilities of Madrasah, level of Madrasahs’ economic viability and ecological friendliness, influence of the level of adequacy of existing resource capabilities on the economic viability and ecological friendliness of Madrasah educational institution in Region XII, Philippines.Important findings of the study revealed that 90% of the Asatids were college graduate in Arabic education, receiving an honorarium of 1,000 pesos a month, high school graduate in Western education, and with a monthly net income of 7,800 – 8,800.Madrasah resource capabilities like physical, instructional, and financial aspect were found to be adequate while manpower capabilities were moderately adequate.Selected Madaris were assessed to have highly sustained their ecological friendliness and economic viability.The factors which had significantly influence the Madrasah economic viability were manpower capabilities and financial aspect of the Madrasah institution. However, ecological friendliness of the Madrasah institution in Southern Philippines was influence by Madrasahs’ resource capabilities like physical facilities, manpower capabilities, and financial aspect.In order to sustain the Madrasah educational system in Mindanao, it is recommended that more funds shall be provided both from local and foreign sources.